Volumetric and Viscometric Study of Amino Acids in Aqueous Solution of Maltose at Different Temperatures - Khanuja, Parvinder; Chourey, V.R. (Asian Journal of Chemistry, 2013)
Density and viscosity measurements were performed for amino acids in 0.05-0.25 M aqueous maltose at 293.15, 303.15 and 313.15 K. The measured values of density and viscosity were used to estimate some important parameters, such as the partial molal volume, the partial molal volume of transfer, the second derivative of the infinite dilution of the standard partial molal volume with temperature, the viscosity B-coefficients, variation of B with temperature, dB/dT, the free energy of activation per mole of solvent amino acid in a ternary system. These parameters were interpreted in terms of solute-solute and solute-solvent interactions and structure making/ breaking ability of solutes in the given solution.